2022
DOI: 10.1097/bpb.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion fractures of the ischial tuberosity in the pediatric athlete: a systematic review and return to sport analysis

Abstract: Apophyseal avulsion fractures of the ischial tuberosity (AFIT) in pediatric athletes are relatively uncommon injuries with treatment and return to sport (RTS) outcomes being largely unknown. The purpose of this review is to perform a systematic review analyzing RTS and predictors of successful RTS for pediatric athletes sustaining AFIT. Studies reporting on athletes strictly under the age of 18 years sustaining an AFIT with reported RTS status were included. RTS was analyzed based on injury acuity, mechanism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(284 reference statements)
0
7
0
Order By: Relevance
“…Avulsion fractures of ischial tuberosity almost always occur in adolescents, in whom the vulnerable unfused epiphysis can be easily avulsed with a sudden and forceful eccentric contraction of the hamstrings[ 5 ]. Avulsion fractures are usually incurred during competitive sports, such as soccer, sprinting, and gymnastics[ 6 ], when the affected leg is forced into hyperflexion of the hip with full extension of the knee[ 7 ]. Avulsion fractures sustained in the course of dancing are uncommon, because dancers often have higher flexibility than athletes who play other competitive sports that require greater strength[ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avulsion fractures of ischial tuberosity almost always occur in adolescents, in whom the vulnerable unfused epiphysis can be easily avulsed with a sudden and forceful eccentric contraction of the hamstrings[ 5 ]. Avulsion fractures are usually incurred during competitive sports, such as soccer, sprinting, and gymnastics[ 6 ], when the affected leg is forced into hyperflexion of the hip with full extension of the knee[ 7 ]. Avulsion fractures sustained in the course of dancing are uncommon, because dancers often have higher flexibility than athletes who play other competitive sports that require greater strength[ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all avulsion fractures can be identified with standard pelvic X-rays[ 11 ]. Nevertheless, the aspecificity of reported symptoms and the lack of awareness of these injuries frequently result in them being misdiagnosed as muscular strains or tendinous tears[ 1 , 6 ]. CT and magnetic resonance imaging scans are useful for the differential diagnosis of avulsion fractures with no or minimal displacement from muscular or tendinous tears[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review evaluating pediatric ischial tuberosity avulsion fractures found that 82% of athletes returned to sport at a mean of 7 months after the injury, with those treated surgically returning at a higher rate of 95% compared with 73% in those treated conservatively. The complication rates were 16% for those patients treated surgically and 33% for those patients treated conservatively 78 .…”
Section: Sportsmentioning
confidence: 93%
“…Categories for data collection for each of the articles meeting inclusion/exclusion criteria included: (a) article information, (b) patient demographics, (c) fracture management, (d) surgical technique, (e) fracture acuity, (f) incidence of nonoperative and surgical complications, as described in prior reviews on apophyseal avulsions [9,10], and (g) RTS rate and timing following injury. The primary outcomes were weighted RTS rates and timing.…”
Section: Methodsmentioning
confidence: 99%
“…Intraclass correlation coefficients (ICCs) using a two-way random-effects model were calculated to compare Pierson and MINORS scores between two authors (blinded for peer review) to assess study quality consistency. All analyses and pooling of outcomes from included case reports and series were conducted in Stata 14.0 (Stata Corp., College Station, Texas, USA) similar to that of prior literature [9][10][11].…”
Section: Data Extraction and Statistical Analysismentioning
confidence: 99%